3D Finite Element Study on Incomplete Osseointegration: Locator Attachment versus Ball Attachment - ElGabry, Hisham S.; Yousief, Salah A.; Moubarak, Amal H.; Eltaftazani, Iman A.; El-Anwar, Mohamed; El Zawahry, Mohamed (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Incomplete implant osseointegration may affect the choice of the type of attachment to ensure less amount of bone resorption, periods of maintenance, and longer implant/attachment life-time. AIM: The aim of this study was to evaluate, using 3D FE analysis (FEA), the influence of two different types of attachments on the rate of bone resorption, need for maintenance and implant/attachment life time in cases of unpredictable osseointegration in various bone types and using different implant angulations. METHODS: Six finite element models were prepared; three for the locator attachment while the other three for the ball attachment. Each of the three models simulates vertical implant and inclined implants by 10° and 20° degrees. Frictional contact between implant and cortical bone simulated the incomplete osseointegration scenario. RESULTS: Non-linear static analysis results showed that locator attachment and its cap may have longer time life in comparison with the ball attachment and its cap. CONCLUSIONS: Both attachments were safe for cortical and spongy bone, while the cortical bone receives less Von Mises stress by up to 33% with the increased implant angulation.